2020
DOI: 10.1021/acsami.0c15456
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Iodine from Nuclear-Fuel-Reprocessing Off-Gas: Influence of Aging on a Reduced Silver Mordenite Adsorbent after Exposure to NO/NO2

Abstract: Iodine radioisotopes released during nuclear fuel reprocessing must be removed from the off-gas stream before discharge. One promising material for iodine capture is reduced silver mordenite (Ag 0 Z). Nevertheless, the adsorbent's capacity will degrade, or age, over time when the material is exposed to other off-gas constituents. Though the overall impact of aging is known, the underlying physical and chemical processes are not. To examine these processes, Ag 0 Z samples were prepared and aged in 2% NO 2 in dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…One major obstacle to the use of Ag adsorbents is, however, their tendency to steadily lose capacity (i.e., age) when they are exposed to other SNF reprocessing off-gas components (e.g., O 2 , H 2 O, NO x ) at elevated temperatures for prolonged periods of time. Our previous studies have focused on the processes governing aging in two prototypical porous Ag adsorbents, Ag 0 Z and reduced Ag functionalized silica aerogel (Ag 0 -aerogel), in gas streams containing the aforementioned off-gas components. Ag 0 -aerogel is a relatively new material developed at Pacific Northwest National Laboratory (PNNL), and its high Ag content and adequate specific surface area aid in iodine capture, making it an appealing alternative to zeolites that have traditionally been the primary focus in this area. , By exposing Ag 0 Z and Ag 0 -aerogel to gas streams containing the aforementioned off-gas components at 150 °C, we found that NO 2 significantly reduced the I 2 capacity for both materials (∼90% reduction after 1 month), , while O 2 , H 2 O, and NO were less impactful (30%–80% reduction for Ag 0 Z and ∼20% reduction for Ag 0 -aerogel after 1 month). , Though the existence of the aging phenomenon is well established, there are still, nevertheless, some discrepancies that arise when attempting to understand its underlying processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One major obstacle to the use of Ag adsorbents is, however, their tendency to steadily lose capacity (i.e., age) when they are exposed to other SNF reprocessing off-gas components (e.g., O 2 , H 2 O, NO x ) at elevated temperatures for prolonged periods of time. Our previous studies have focused on the processes governing aging in two prototypical porous Ag adsorbents, Ag 0 Z and reduced Ag functionalized silica aerogel (Ag 0 -aerogel), in gas streams containing the aforementioned off-gas components. Ag 0 -aerogel is a relatively new material developed at Pacific Northwest National Laboratory (PNNL), and its high Ag content and adequate specific surface area aid in iodine capture, making it an appealing alternative to zeolites that have traditionally been the primary focus in this area. , By exposing Ag 0 Z and Ag 0 -aerogel to gas streams containing the aforementioned off-gas components at 150 °C, we found that NO 2 significantly reduced the I 2 capacity for both materials (∼90% reduction after 1 month), , while O 2 , H 2 O, and NO were less impactful (30%–80% reduction for Ag 0 Z and ∼20% reduction for Ag 0 -aerogel after 1 month). , Though the existence of the aging phenomenon is well established, there are still, nevertheless, some discrepancies that arise when attempting to understand its underlying processes.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of new Ag species after aging is, for example, a key feature in our previous studies though these aging byproducts may or may not directly reduce the I 2 capacity of the adsorbent. For instance, Wiechert et al reported that molecular Ag nitrate (AgNO 3 ) was generated as a byproduct of aging in Ag 0 Z samples exposed to NO x -containing (NO and NO 2 ) gas streams . AgNO 3 is a well-documented I 2 -favored species and contributes to a portion of I 2 adsorption at the early stages of Ag 0 Z aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial step in assessing oxidation potential is to conduct aging experiments, whereby candidate sorbents are subjected to relevant gas streams expected in the process stream for extended time periods and the sorbent performance is evaluated after these aging experiments. Aging experiments in 2% NO 2 in dry air and 1% NO in N 2 streams at 150 °C (for up to 6 months) were noted to drastically reduce the iodine capacity of reduced silver mordenite (Ag 0 Z) in a study by Wiechert et al (2020) , whereby Ag 0 is oxidized to form molecular nitrates that are believed to be on the surfaces of the mordenite crystals. In their study, X-ray absorption spectroscopy was used to verify that a majority of the Ag present in the aged samples was in the oxidized (Ag + ) state.…”
Section: Introductionmentioning
confidence: 99%
“…A main challenge that remains to be resolved is the effective control of the radioactive product emissions that potential reprocessing technologies produce. These complex off-gas streams include the long-lived radioisotope 129 I, which readily volatilizes and partitions into reprocessing off-gas streams …”
mentioning
confidence: 99%